Information system sophistication's for enhancing the performance of women technopreneur business - Othman, Azizah; Bohari, Abdul Manaf; Fuad, Nurwahida (2013)
Theoretically, technopreneurs are technological based entrepreneurs who are into the core businesses involving technology-based sector.They make use of such kind of technology to come out with new or innovative products through a process of development and commercialization.The businesses are generally marked with high growth potential and high leverage of knowledge and intellectual property.Potential technopreneur must be equipped with information system (IS) sophistications where it is vital important to sustain their long live of business.Practically, there are sixth types of IS, common identified as Executive Information System (EIS), Management Information System (MIS), Decision Support System (DSS), Knowledge Information System (KWS), Marketing Information System (MKIS), and Transaction Information System (TPS) where final aimed to sustain the performance of technopreneurs business.However, there are questions arises about capability and suitability of IS resources in uses of technopreneurs business, as well as to gear-up the business performance.The objective of this paper is to overview the fundamental concept, capability and constrains of every types of IS sophistications with specific reference to capability and suitability to the technopreneurs business.Un-structured interview approach has been used to explore the insight of IS sophistications. In general, this study found that most IS sophistications have unique capability to support and manage the performances of the technopreneurs business.Specifically, DSS is seen as important IS sophistications to support decision making for execute specific decision although the DSS still lacks on certain part.The paper is suggest a guideline on how do develop and implementing the IS as important platform for the future growth of the technopreneurs business.